2010
DOI: 10.1177/1469787410365650
|View full text |Cite
|
Sign up to set email alerts
|

Peer-mentoring undergraduate accounting students: The influence on approaches to learning and academic performance

Abstract: This article considers the impact of a student peer-mentoring programme (the Mentor Accountant Project, MAP) on first-year undergraduates' academic performance. The development of MAP was informed by reference to extant literature; it relies on the voluntary services of third-year students who then act as mentors to first-year student mentees in an undergraduate degree programme. The impact of MAP in two Scottish universities is measured by reference to the changes in the approaches to learning and the academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 32 publications
1
53
0
2
Order By: Relevance
“…Previous research in the accounting education literature found it difficult to support change by accounting students from surface to deep learning (English et al, 2004;Hall et al, 2004;Ballantine et al, 2008;Fox et al, 2010). These studies involved limited interventions to support deep learning with apparently many aspects of the design and delivery of the courses involving traditional approaches that could be seen as supporting surface learning (Boyce et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in the accounting education literature found it difficult to support change by accounting students from surface to deep learning (English et al, 2004;Hall et al, 2004;Ballantine et al, 2008;Fox et al, 2010). These studies involved limited interventions to support deep learning with apparently many aspects of the design and delivery of the courses involving traditional approaches that could be seen as supporting surface learning (Boyce et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has found supporting deep learning to be a challenging issue for accounting students (English et al, 2004;Hall et al, 2004;Ballantine et al, 2008;Fox et al, 2010); and also for students in a range of other disciplines including, for example, education, science, psychology, nursing and medicine (Baeten et al, 2010). Also, these previous studies did not include interventions designed to support students to experience three preconditions for them to experience deep learning: high-level relevance structures, high-level conceptions of learning and intrinsic motivation.…”
Section: This Study Has Addressed the Following Research Questionmentioning
confidence: 99%
“…Fourthly, other specific theoretical constructs of mentoring program, such as learning ethics and delivery mode should be considered because they have widely been recognized as an important link between mentoring relationship and many aspects of individual attitudes and behaviors (Davis 2007;Dutton 2003;Sa'id 1998). Finally, other outcomes of mentee like their psychosocial state, self-efficacy, transfer of knowledge, skills and ability, positive change, and career help should be considered because they have received a lot of attention in mentoring program research literature (Fox et al 2010;Hansford & Ehrich 2006;Ismail et al 2006;Ismail & Ridzuan 2012). The importance of these issues needs to be further discovered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…In organizations, formal and informal mentoring programs are viewed as equally important, but informal mentoring programs are often implemented to complement and strengthen formal mentoring programs in order to achieve organizational strategies and goals (Friday & Friday 2002;Hansford & Ehrich 2006;Hansford et al 2003: Ismail et al 2005Ismail et al 2006). A review of current higher education student development program literature highlights that effective mentoring programs have two salient practices, i.e., communication and support (Bernier et al 2005;Ismail & Ridzuan 2012;Tennenbaum et al 2001 (Allen et al 2005;Fox et al 2010;Ismail et al 2005;Ismail et al 2006;Santos & Reigadas 2005;Stewart & Knowles 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation